Vascular Age as a Cardiovascular Risk Marker in Asymptomatic Patients with Type 2 Diabetes - Palma CCSSV; Lopes PM; Silva ELC; Bevilaqua MFM; Bomfim AS; Gomes MB (Diabetes, Metabolic Syndrome and Obesity, 2020)
Cátia Cristina Silva Sousa Vergara Palma,1 Pablo Moura Lopes,2 Eliete Leão Clemente Silva,1 Maria de Fátima da Matta Bevilaqua,1 Alfredo de Souza Bomfim,2 Marilia Brito Gomes1 1Department of Internal Medicine, Diabetes Unit, State University Hospital of Rio de Janeiro, Rio de Janeiro, Brasil; 2Department of Internal Medicine, Cardiology Unit, State University Hospital of Rio de Janeiro, Rio de Janeiro, BrasilCorrespondence: Cátia Cristina Silva Sousa Vergara PalmaDepartment of Internal Medicine,Diabetes Unit, Rio de Janeiro State University (UERJ), Boulevard 28 de Setembro, 77- 3º Andar - Vila Isabel, Rio de Janeiro, RJ 20551-030, BrazilTel +55 212 868 8224Email catiasousapalma@gmail.comAim: There is a wide variety of cardiovascular outcomes in patients with type 2 diabetes (T2DM), even in asymptomatic individuals. Carotid intima-media thickness (CIMT) is a marker of subclinical atherosclerosis and can be considered as a predictor of cardiovascular risk (CVR). The aim of this study was to evaluate the relationship between CIMT-determined vascular age (VA), CVR scores, and thyroid function in asymptomatic patients with T2DM.Patients and Methods: Clinical laboratory and CIMT parameters were measured in 154 asymptomatic patients with T2DM. The Framingham risk score (FRS) was performed with chronological age (CA) and with VA. A multinomial logistic regression model was used to analyze variables related to CVR reclassification.Results: The use of CIMT-determined VA led to the reclassification of 54 (35.52%) out of 152 asymptomatic T2DM patients, being 20 (37.03%) to a lower categorical risk and 34 (62.96%) to a higher categorical risk according to FRS. The variables that were associated to reclassification to a higher categorical risk were positive family history (FH) of premature coronary artery disease (p=0.046), FH of thyroid disease (p=0.010), use of statins (p=0.027), and free T4 levels (p=0.009).Conclusion: VA determined from CIMT allowed the reclassification of the CVR in asymptomatic T2DM patients. FH of premature CAD, FH of known thyroid disease, use of statins, and free T4 levels were associated to a reclassification into a higher risk category. The use of doppler to perform CIMT measure is currently more accessible, especially in a low-middle income country like Brazil. However, further prospective studies must be performed to establish the predictive values of CIMT on atherosclerosis and how thyroid function acts like cardiovascular risk marker on CVR scores.Keywords: vascular age, type 2 diabetes, cardiovascular risk, CIMT